62 Follow-up of patients with isolated active ileitis: increasing development of overt crohn's disease over time. (5th April 2017) - Stack, R; O'Donnell, S; O'Morain, N; Hussey, M; O'Connor, A; Breslin, N; Alakkari, A; McNamara, D; Ryan, BM
Abstract : Background: Increased TI intubation at colonoscopy had led to increased identification of mild ileal inflammation. Patients with co-called Isolated Active ileitis (IAI) have mild TI inflammation, no chronicity on histology, and do not fulfil criteria for a diagnosis of Crohn's Disease (CD). Causes include CD, NSAID use or infection. The natural history of IAI has remained unclear. Aim: Long term follow up of a cohort of patients diagnosed as IAI, to assess evolution to CD, persistent IAI and Self-Limiting Ileitis (SLI). Method: IAI patients were reviewed at a 10 year interval by means of clinical follow up, endoscopy, histology and small bowel imaging (SBI). Results: 50 patients; Median age 48 years; 16/50 (32%) male. At time of follow up, 29/50 (58%) had a follow up ileocolonoscopy with 16/29 (55%) showing persistent ileitis on histology. 38/50 had formal SBI with inflammatory changes on 11/38 (29%). Of the original cohort, SLI, persistent IAI and CD was reported in 7/50 (14%), 7/50 (14%) and 14/50 (28%), respectively. 22/50 patients were lost to follow up. 4 patients developed strictures and 3 required surgery. Predominant presenting symptoms included pain and diarrhoea in all groups, with no statistical difference in smoking, NSAID use and family history amongst the 3 subgroups. Conclusions: Over time a significant portion of patients with IAI evolve to overt small bowel CD. Neither presenting complaint nor clinical risk factors were predictive of disease progression, suggesting these all patients should be under surveillance for disease progression.